Predatory Publishing in Nursing. (July 2019) - Milton, Constance L.
Predatory publishing is a contemporary term that refers to dubious open access publishing where there are questionable practices of marketing, business, and alteration of peer-review publishers' practices. This article begins a straight-thinking discussion with recommendations intended to inform present and future scholars of the discipline of nursing of these alarming developments in the publishing arena.